2009
DOI: 10.1111/j.1365-2591.2008.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different laser systems to kill Enterococcus faecalis in aqueous suspension and in an infected tooth model

Abstract: The laser systems as well as PAD were less effective than NaOCl in reducing E. faecalis, both in aqueous suspension and in the infected tooth model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
4
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 44 publications
7
73
4
10
Order By: Relevance
“…6 Theoretically, laser energy may not only kill bacteria directly, but also activate the irrigant to enhance its bactericidal actions. 8,23 However, no difference in bacterial reduction was found between the PIPS + NaOCl, NaOCl, and NaOCl + EDTA groups in the present study. This is probably because of the lower volume of NaOCl being used in the PIPS + NaOCl group as compared with the other groups.…”
Section: Discussioncontrasting
confidence: 67%
“…6 Theoretically, laser energy may not only kill bacteria directly, but also activate the irrigant to enhance its bactericidal actions. 8,23 However, no difference in bacterial reduction was found between the PIPS + NaOCl, NaOCl, and NaOCl + EDTA groups in the present study. This is probably because of the lower volume of NaOCl being used in the PIPS + NaOCl group as compared with the other groups.…”
Section: Discussioncontrasting
confidence: 67%
“…Single irradiation with a 980-nm diode laser operated at a power output of 1500 mW in the continuous wave (CW) mode (Group 1) resulted in a significant reduction of E. faecalis CFU/mg in comparison with the control group (Group 5). Complete E. faecalis eradication was demonstrated in the 5.25% NaOCl-irrigated group (Group 4), which is in accordance with other studies [23,25]. This effect results from the antimicrobial action of hypochlorous acid and active chlorine [26].…”
Section: Discussionsupporting
confidence: 90%
“…Different laser devices are used currently in root canal treatment [4,22,23]. The high power diode laser, emitting at a wavelength of 980 nm, was first introduced for use in endodontics in 1997 [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An optical fiber with 200 μm diameter and 1mm shorter that the working length is placed inside the canal, starting irradiation with circular movement in the apical-coronal direction. 52 Some studies suggested applying this technique in canals filled with irrigants such as EDTA, citric acid or NaOCl reduces the thermal side effects. 53 It should be considered that irradiation of the Nd:YAG and diode laser can create fusion and superficial re-solidification in the dentine with a clear glazed surface.…”
Section: Lasersmentioning
confidence: 99%